2010
DOI: 10.1038/ismej.2010.100
|View full text |Cite
|
Sign up to set email alerts
|

Possible interactions between bacterial diversity, microbial activity and supraglacial hydrology of cryoconite holes in Svalbard

Abstract: The diversity of highly active bacterial communities in cryoconite holes on three Arctic glaciers in Svalbard was investigated using terminal restriction fragment length polymorphism (T-RFLP) of the 16S rRNA locus. Construction and sequencing of clone libraries allowed several members of these communities to be identified, with Proteobacteria being the dominant one, followed by Cyanobacteria and Bacteroidetes. T-RFLP data revealed significantly different communities in holes on the (cold) valley glacier Austre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
191
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 156 publications
(207 citation statements)
references
References 46 publications
13
191
1
Order By: Relevance
“…Their presence has been connected with decreased albedo of cryoconite sediment, higher water temperatures, and a subsequent increase in microbial activity (Stibal et al 2006;Edwards et al 2011). Our data suggest that the PHAC/TC ratio and tetrazolium reducing activity in Ecoplates increased in cryoconite samples in which SUVA measurements were elevated.…”
Section: Significant Environmental Controlssupporting
confidence: 48%
See 1 more Smart Citation
“…Their presence has been connected with decreased albedo of cryoconite sediment, higher water temperatures, and a subsequent increase in microbial activity (Stibal et al 2006;Edwards et al 2011). Our data suggest that the PHAC/TC ratio and tetrazolium reducing activity in Ecoplates increased in cryoconite samples in which SUVA measurements were elevated.…”
Section: Significant Environmental Controlssupporting
confidence: 48%
“…Many researchers investigating glacial microbiota have collected samples along a transect like ours (Mindl et al 2007;Uetake et al 2010;Edwards et al 2011;Zarsky et al Fig. 5 Principal component analysis of microbiological data in surface ice (black diamonds) and cryoconite samples (circles).…”
Section: Spatial Variation Issuementioning
confidence: 99%
“…In the Arctic, Irvine-Fynn et al (2012) demonstrate that water flow through the near-surface porous ice ("weathering crust") facilitates microbial transport downglacier. Moreover, Edwards et al (2011) infer that surface hydrology modulates cryoconite bacterial community structure and function. As Cook et al (2015) discuss, cryoconite holes penetrate the weathering crust and offer long term storage for mineral and organic matter, as well as being natural piezometers indicative of meter-scale weathering crust hydrology.…”
Section: Biocryomorphologymentioning
confidence: 99%
“…These species are considered opportunistic organisms with wide ecological roles and strong colonizing potential, rather than glacial specialists. Although one 16S rRNA gene-based clone library study suggested that cyanobacteria are not predominant bacterial members within High Arctic cryoconite holes (Edwards et al 2011). A recent study employing deep sequencing showed that cyanobacteria, namely Microcoleus and Phormidium were the most abundant bacterial groups in cryoconite located in Svalbard located in the high Arctic (Edwards et al 2011).…”
Section: Cryoconitesmentioning
confidence: 99%